Reward and Punishment as Educational Strategies in Enhancing Students’ Discipline in Congregational Qiyamullail Prayer - Dini Permana Sari; Asraffun Zuam Maulana (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: This study aims to describe the implementation of reward and punishment strategies in improving students’ discipline in performing congregational qiyamullail prayer at Integrated Islamic Junior High School Insan Mandiri Greenville boarding school. Methodology: This study employed a qualitative method using a Participatory Action Research (PAR) approach. Data were collected through structured observation, in-depth interviews, and documentation. The participants consisted of boarding students, dormitory head, worship coordinator, and teachers, selected using purposive sampling technique. Main Findings: The results indicate that reward and punishment effectively improved students’ discipline in congregational qiyamullail prayer. Participation increased by 18.75% through verbal appreciation, 27.1% with simple material rewards, 43.75% through religious reprimands, and reached 95% after strengthened punishment involving cleaning duties. Novelty/Originality of this study: This study offers empirical evidence on the structured application of reward and punishment within Islamic boarding school worship activities using a PAR approach, highlighting a progressive and educational disciplinary model that integrates spiritual development with behavioral reinforcement strategies.